An Analysis of Network Effects and the Financial Performance of Online Learning Platforms - Marian Stan; Mihai Ciobotea (Ovidius University Annals: Economic Sciences Series, 2022)
With the advances in the cloud computing, the Internet, and mobile communications technologies in the last two decades, a large number of business opportunities have emerged. The online learning providers bring together individuals and organizations so they can interact in ways not otherwise possible in order to generate value and utility. The global online learning market represents a growing and attractive opportunity for the incumbents from this sector. All of the analyzed platforms have recorded consistent growth over the years. Our research aims to develop a better understanding about the network effects and the financial performance of the major online learning platforms. We have focused on the context of Massive Open Online Course (MOOC) platforms since they have a higher impact on the online learning communities, analyzing their market segments and financial performance.